Efficiency Analysis of Methanol Usage for Marine Turbine Power Plant Operation Based on Waste Heat Chemical Regeneration - Cherednichenko O.C. (Problems of the Regional Energetics)
The issues of improving the efficiency of methanol usage as a promising marine power plant fuel with low carbon content are discussed. The main aim of the research is an analysis of characteristics of advanced marine gas turbine power plants with the combined thermodynamic and thermochemical regeneration of waste heat. The possible methanol conversion at the expense thermochemical heat regeneration of marine engines recoverable resources has been revealed. The analysis of parameters influences of the waste heat recoverable resources, as well as restrictions related to the engine system of gas fuel injection, on the efficiency of methanol conversion has been carried out. It was demonstrated that the simulation of methanol steam conversion processes results in the pressure increase in the reactor, which, in its turn, causes a shift of conversion efficiency process towards higher temperature area. The calculation scheme of steam injection gas turbine plant with the joint thermodynamic and thermochemical regeneration of waste heat is demonstrated. The results of mathematical simulation of the processes in regeneration plant under the 3.4 MW constant capacity and heat exchanger thermal ratio of 0.85 were obtained. The cycle optimization has been based on the efficiency of plant under the conditions of variation of water/methanol ratio and gas temperatures in thermochemical regenerator. The efficiency increase constituted 4% relative to characteristics of the base engine operating on methanol. The estimation of carbon content in produced syngas has shown that thermochemical regeneration of methanol conversion by using the waste heat can reduce the energy efficiency by 1.5 times.